Antithrombotic treatment gap among patients with atrial fibrillation and type 2 diabetes. (15th August 2019) - Guimarães, Patrícia O.; Peterson, Eric D.; Stevens, Susanna R.; Lokhnygina, Yuliya; Green, Jennifer B.; McGuire, Darren K.; Holman, Rury R.; Lopes, Renato D.
Abstract: Background: We investigated the use of different antithrombotic therapies at baseline among patients with a history of atrial fibrillation (AF), type 2 diabetes, and established atherosclerotic cardiovascular disease (ASCVD) enrolled in the Trial Evaluating Cardiovascular Outcomes with Sitagliptin (TECOS). Methods: TECOS participants with a history of AF were stratified by CHA2 DS2 -VASc score and their antithrombotic use evaluated. Cox proportional hazards models were employed to explore possible associations between history of AF and prespecified clinical outcomes after adjusting for key baseline characteristics. Results: Of the 14, 671 TECOS participants, 1167 (8%) had a history of AF, of whom 51.6% were using vitamin K antagonists (VKA); 31.2% used VKA alone, 16.9% used aspirin plus VKA, 1.8% used clopidogrel plus VKA, and 1.7% used aspirin and clopidogrel plus VKA. Aspirin was used by 56.8%: 30.9% used aspirin alone and 7.3% aspirin plus clopidogrel. Clopidogrel alone was used by 2.9%, and 7.3% were not using any antithrombotic medication. Participants with a history of AF had a higher risk of cardiovascular events, including hospitalization for heart failure and all-cause mortality, than those without AF. White, older men with prior myocardial infarction, heart failure, peripheral artery disease, or prior stroke were more likely to develop new-onset AF than others without these characteristics. Conclusions: Almost half of high-risk AF patients with diabetes and established ASCVD in TECOS were not treated with anticoagulation therapy despite clear guideline recommendations for such therapy, highlighting the challenge and potential for clinical improvements in managing these patients in clinical practice. Clinical Trial Registration : URL:http://www.clinicaltrials.gov . Unique identifier:NCT00790205 . Highlights: Afib and type 2 diabetes are associated with adverse cardiovascular outcomes. We examined OAC use by TECOS patients with Afib, ASCVD, and type 2 diabetes. OAC use by these high-risk patients is much less than guideline recommendations.